Determinants of technology acceptance towards 5g mobile repurchase intention: an empirical Study on Malaysian customer satisfaction - Kaniz, Afroza; Ulfy, Mohammad Arije; Haque, A. K. M. Ahasanul (Elsevier, 2025)
Abstract This study investigates the elements influencing consumer satisfaction and repurchase intention in the context of 5G technology adoption. The study uses the Technology Acceptance Model (TAM) as its theoretical framework within a positivist design, emphasising deductive reasoning and empirical evidence to predict human behaviour, employing a methodical methodology matched with research as a means of acquiring and analysing data. It emphasises experimental study, which allows for variable isolation and causal inference while adhering to scientific norms. The survey will use a sample size of 125 respondents and focus on Klang Valley, Malaysian urban regions and tech-savvy smartphone users with 5G access. Data collected using a 5-point Likert scale and convenience sampling via online questionnaires, allowing for an organised examination of customer retention behaviour in telecoms. The research constructs were painstakingly specified, conceptualised, and operationalised, including perceived usefulness, perceived ease of use, and network effects, in addition to satisfaction and repurchase intention. Afterwards, the collected data was examined using SPSS 26 & AMOS 23 software. Through different testing, rigorous preparatory analysis ensured instrument reliability and validity. The findings revealed that customer satisfaction (CS) had an average variance extracted (AVE) value of 0.474 initially, which improved to 0.594 after item adjustments. Similarly, repurchasing intention (RI) showed an AVE value of 0.665, indicating robust convergent validity. The AVE values of the other parameters, PU 0.590, PEOU 0.554 & NEf 0.602, were found satisfactory. In summary, this study adheres to a rigorous research method by using an online self-administered questionnaire. Its painstaking design, testing, and early analysis create a solid platform for future data collecting and analysis, providing genuine insights on 5G technology uptake and repurchase intention.